Recent Progress in Nanostructured Functional Materials and Their Applications - Boaventura, Peter; Pereira, Javalina; Vilar, Emilia; Lofrano, Giusy; Caroteto, Robert (Journal of Functional Materials and Applied Engineering, 2024)
Nanostructured functional materials represent a revolutionary class of substances engineered at the atomic and molecular scale (1-100 nm) to exhibit exceptional properties not found in their bulk counterparts. Spanning the past decade, this detailed survey traces the striking advances in how such materials are prepared, analyzed, and deployed across a broadening range of uses. Our survey spans pivotal material families—metallic nanocrystals, quantum dots, atom-thin 2D layers, MOFs, COFs, and their blended architectures—underscoring how each unique framework governs property and performance.Significant breakthroughs have been achieved in synthesis techniques such as confined self-assembly, seed-mediated growth, chemical vapor deposition, and solution processing, enabling precise control over size, shape, composition, and architecture. These materials have demonstrated transformative potential across diverse fields including energy storage and conversion (batteries, supercapacitors, catalysts, photovoltaics), electronics and photonics (sensors, transistors, LEDs), environmental remediation (adsorption, catalysis, filtration), and biomedicine (drug delivery, theranostics, biosensing). Particularly noteworthy are the developments in photonically active cellulose nanocrystal filaments, biodegradable near-infrared-responsive shape memory implants, and ultra-black nanocomposites for space applications. Despite these advancements, challenges remain in scalability, reproducibility, nanotoxicity, and integration into functional devices. Future research directions focus on computational design using AI and machine learning, multifunctional smart materials, biomimicry, and sustainable nanotechnology. This review highlights how nanostructured functional materials continue to drive innovation across scientific disciplines and technological applications.